"Why did you really do it?" A mixed‐method analysis of the factors underpinning motivations to register as a body donor. Issue 6 (15th May 2018) - Cornwall, Jon; Poppelwell, Zoe; McManus, Ruth
Abstract : Individuals who register as body donors do so for various reasons, with aiding medical science a common motivation. Despite awareness of several key reasons for donation, there are few in‐depth explorations of these motivations to contextualize persons' reasons for donating. This study undertakes a mixed‐method exploration of motivations for body donation to facilitate deeper understanding of the reasons underpinning donor registration. A survey of all newly registered body donors at a New Zealand university was performed over a single year. The survey included basic demographic information, a categorical question on reason for donation, a free‐text question on donation motivation, and a free‐text question allowing "other" comments on body donation. Basic statistical analysis was performed on demographic and categorical data, and thematic analysis used on free‐text responses. From 169 registrants, 126 people (average age 70.5 years; 72 female) returned completed surveys (response rate 75%). Categorical data indicate a primary motivation of aiding medical science (86%). Fifty‐one respondents (40%) provided free‐text data on motivation, with other comments related to motivation provided by forty‐one (33%). Common themes included reference to usefulness, uniqueness (pathophysiology and anatomy), gift‐giving, kinship, and impermanence of the physical body. Consistent with previous studies, the primary reason for body donation was aiding medical science, however underpinning this was a complex layer of themes and sub‐themes shaping motivations for choices. Findings provide important information that can guide development of robust informed consent processes, aid appropriate thanksgiving service delivery, and further contextualize the importance of medical professionals in body donation culture.